The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1034/j.1600-0463.2002.100406.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular heterogeneity of fluconazole‐resistant and ‐susceptible oral Candida albicans isolates within a single geographic locale

Abstract: The emergence of drug-resistant Candida albicans in immunocompromised patients is common. A disconcerting aspect of this phenomenon is the rapid emergence of C. albicans strains that are resistant to a widely used azole drug, fluconazole (FLZ). To understand the origin of FLZ-resistant yeast isolates, we investigated molecular profiles of 20 geographically related oral C. albicans isolates using three genotyping methods: randomly amplified polymorphic DNA-PCR, with six different primers (OBU1, OBU2, OBU3 RSD6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…Our result also showed that the DNA type of each isolate was patient specific and associated with ABC type and decade of isolation, but not associated with anatomical source of isolation, hospital origin, or fluconazole resistance patterns, which is in accordance with previous reports (8).…”
Section: Discussionsupporting
confidence: 81%
“…Our result also showed that the DNA type of each isolate was patient specific and associated with ABC type and decade of isolation, but not associated with anatomical source of isolation, hospital origin, or fluconazole resistance patterns, which is in accordance with previous reports (8).…”
Section: Discussionsupporting
confidence: 81%
“…Genotypic characterization in groups has been defined by Xu et al 28 for resistant isolates to fluconazole, who observed that resistant strains to this drug were genetically more similar to each other than they were to susceptible strains. Dassanayake et al 18 showed that, of the 20 isolates studied, only one resistant isolate presented the same profile as the susceptible one.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works show that alterations in the ERG11 gene, responsible for ergosterol production, limit hyphal formation presumably because of the lack of ergosterol 27 . Although fluconazole is the most used antifungal agent for the treatment of infections caused by C. albicans, an increased number of resistant isolates have been observed 18 . Therefore, detection of resistance among isolates is considered of great importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For RAPD, a single short primer of arbitrary sequence Ca2 (5'-GCGATCCCCA-3') was used to bind randomly to the target DNA resulting in the amplification of fragments of unknown sequence (15). The amplification reaction was carried out under the following conditions: 94°C for 5 minutes, followed by 35 cycles of 94°C for 30 seconds, 37°C for 30 seconds, 72°C for 90 seconds, and final extension at 72°C for 10 minutes.…”
Section: Molecular Analysismentioning
confidence: 99%